Leadership in Fury Movie Directed by David Ayer - Unpris Yastanti; Virky Septian Dwi Putra (Makassar State University, 2019)
The purpose of this study is to identify leadership in Fury movie directed by David Ayer. This study used descriptive qualitative approach. The result of this study: (1). The main character is the leader of his team. He makes a strategy and he tells the strategy to his team. (2) Leadership style of the main character in the Fury movie are autocratic and bureaucratic leadership style. (3) The moral message in the movie are a virtue, sacrifice and religious man in doing their task in the battlefield.